PENGEMBANGAN MODEL PEMBELAJARAN TEKS ANEKDOT DENGAN STAD DAN MAKE A MATCH PADA SISWA KELAS X SMA - NFN Suharti (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2019)
This development aims to create a product of anecdote learning model book based on STAD and Make A Match on the tenth grade senior high school students. It can be used to facilitate teachers and students to identify the structure of anecdote. It uses Research and Development/R&D of Dick and Carey’s learning model. The results show that it has fulfilled the standard validated by material expert test, linguist test, educational practitioner test, and media expert test with the average score of 92, very feasible/very good criteria. The students’ learning outcomes of the experimental group are excellent with the average of individual cognitive, individual affective, and the group affective score of 96. The students' learning outcomes of the field test group are excellent with the average of individual cognitive, individual affective, and group affective score of 97. The percentage of teachers and students’ response rate are 96%, excellent qualifications. It applies qualitative descriptive and descriptive statistical analysis. Based on the development findings, it can be concluded that the development of anecdote learning with STAD Model and Make A Match on the tenth grade senior high school students can be employed by teachers in the classroom learning.